Buta Senja: Hubungannya Dengan Asupan Vitamin A di Indonesia - Evan Christian Christian; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Night blindness is a disorder of the eyes where the eyes cannot function properly in low light or inadequate lighting conditions. This occurs due to dysfunction of the rod cells present in the retina of the eye. Rod cells play a crucial role in vision and are closely related to the availability of vitamin A in the body. Vitamin A is an essential micronutrient for the body and plays an active role in a person’s vision. Vitamin A works in conjunction with rhodopsin in the mechanism of vision. Vitamin A can produce rhodopsin and regulate vision mechanisms through several mechanisms, one of which is the conversion of the cis chain to trans. Vitamin A deficiency can disrupt a person’s vision. Research shows that there are still many children in the world and in Indoneisa who suffer from vitamin A deficiency. The WHO estimates that around 190 million children worldwide suffer from vitamin A deficiency. Studies in Central Java shows that Indonesia still experiences vitamin A deficiency, with about 60% of children having serum retinol levels below normal. Low serum retinol is indicator of a person’s vitamin A deficiency, The use of vitamin A supplements is important in preventing night blindness. Research shows that the use of additional vitamin A supplements can be done since infancy, by providing supplements to newly delivering mothers, so that the vitamin A supplements consumed by the mother can increase the retinol level in the colostrum of mother’s milk that will be consumed by the child.